QUALITY CONTROL STUDIES OF SIX HERBAL PRODUCTS MARKETED WITHIN ZARIA METROPOLIS - Awwalu, S; Usman, M.A; Muaz, M (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Several reports have shown toxicity of herbal products due to adulteration and/or toxic components. The aim of this research is to conduct quality control studies on six different herbal products marketed in Zaria metropolis. Samples were purchased and then coded. Moisture content and ash values were determined using World Health Organisation, 2011 method while elemental analysis (Pb, As, Cd, Zn and Fe) was conducted using MP-AES after nitric acidhydrochloric acid (1:3) digestion. The moisture contents (2.37-5.46 %) were within the acceptable limit of 10 %. Samples were pure with no likelihood of adulteration as indicated by the low values of total ash (1.8-11 %), water soluble ash (0.2-5 %) and acid insoluble ash (0.5-2 %). Samples were also found to contain Zn (1-13 ppm) within the permissible limit while As was not detected by the method. The concentrations of Pb (2.53-13.27 ppm) and Cd (0.23-2.37 ppm) were within the permissible limit with the exception of HP3 and HP3-HP6 respectively. Samples were rich in iron content (1848-8108 ppm). Two out of the six herbal products were found to be safe for consumption.